A Systematic Literature Review of Accounting Information Systems Implementation Success Factors - Andi; Bahiroh, Eloh; Mulyani, Ana Susi (Accounting Studies and Tax Journal (COUNT), 2024)
This study aims to investigate the influence of factors related to Accounting Information Systems (AIS) on the level of innovation in organizations. The factors analyzed include the characteristics of the Accounting Information System (AIS) for innovation, resource allocation and integrated reporting, the quality of the Accounting Information System, and the role of Strategic Management Accounting. Data was collected through surveys and analyzed using a systematic literature review method approach. The research results show that AIS characteristics that support innovation, appropriate resource allocation, AIS quality, and the role of Strategic Management Accounting have a significant positive impact on the level of innovation in the organization. These findings emphasize the importance of using an Accounting Information System that supports innovation in improving the innovative performance of an organization.